Hopelessness and mental disorders in nursing professionals of cancer services (Research, Society and Development, 2020)
Objective: This study analyzed the presence of hopelessness and its relationship with mental disorders, in nursing professionals who work in oncology services. Method: Descriptive and cross-sectional study carried out with 89 nursing professionals working in specialized services in oncology using the instruments: General identification form, Beck's Hopelessness Scale and Mini International Neuropsychiatric Interview (Brazilian version 5.0.0). Results: Study carried out with 89 nursing professionals. The results revealed that nursing professionals presented minimum hopelessness. There is an association between hopelessness and pre-existing illness (ρ= 0.00), drug treatment (ρ = 0.01), psychiatric follow-up (ρ = 0.00) and some mental disorders [major depressive episode (ρ= 0.02), major depressive episode with melancholic characteristics (ρ= 0.02), dysthymic disorder (ρ= 0.01), agoraphobia (ρ = 0.02), social phobia (ρ= 0.00), risk of suicide (ρ= 0.00), alcohol dependence (ρ = 0.02), substance dependence (ρ= 0.00), antisocial personality disorder (ρ = 0.02) and psychiatric comorbidities (ρ= 0.02)]. Mild hopelessness (21.3%) was evidenced in depression, agoraphobia, panic disorder, risk of suicide, alcohol use and antisocial personality disorder, while moderate hopelessness (1.1%) was present in social phobia and use of psychoactive substances. Conclusion: There was observed an association between hopelessness and some mental disorders in nursing professionals. It is need to carry out activities that promote the well-being of nursing professionals who work in the oncology sectors. Psychological counseling is essential for maintaining mental health.